Danau Diatas Water suitability for Osphronemus Gouramy in Keramba System at Nagari Alahan Panjang, Lembah Gumanti sub-district - JUSAR, IRFAN; Edial, MT, Drs. Helfia; S.Si, M.Sc., Farida (Pendidikan Geografi, 2014)
ABSTRACKDanau Diatas located in di Nagari Alahan Panjang Kecamatan Lembah Gumanti sub district is a common water resource that has an important role for the people living around. Danau Diatas water utilization by local people covering different aspects of life. sugh as cage fish farming, fishing area, water the fields, and household activities. The purpose of fish farming is to produce fish in larger quantities than the natural life. This study aimed to obtain information, the data, analyze, discuss and express about: (1) physical condition of the water Danau Diatas for carp fish farming cage systems which include temperature, and turbidity. (2) water chemistry conditions Danau Diatas for osphronemus gouramy fish farming cage systems which include pH, Dissolved Oxygen (DO), carbon dioxide (CO2) and ammonia (NH3). This study compares the results of the analysis are obtained directly from the field and laboratory with water quality standards for aquaculture. The samples were tested in the north, south, west, east and middle part of Danau Diatas. The results of research on the physical and chemical parameters deskiptif tabulation and analyzed and then compared with the water quality standards for aquaculture. The results of the study are as follows: (1) Water Quality Danau Diatas for osphronemus gouramy fish farming cage systems in physics, namely water temperature Danau Diatas meet the requirements for water temperature of all samples tested was in the range of 20 - 320C and water transparency also meet the requirements of 25-50 cm. (2) Water Quality Danau Diatas for fish farming chemically meet requirements that include pH, Dissolved Oxygen (DO) for all parts meet the requirements while carbon dioxide (CO2) and ammonia (NH3) for all the samples did not meet the requirements for the cultivation of carp.